Innovazione tecnologica e cambiamento dell'università - Antonio, Calvani (Strumenti per la didattica e la ricerca, 2003)
It is by now common knowledge that one of the aspects upon which the survival of the University depends is how it will make the best possible use of the new technologies (e-learning). Despite the acceptance of this principle, difficulties arise when one attempts to proceed from the mere declaration to actually planning activities and putting them into effect. This research, the result of collaboration between teachers and researchers of the Educational Science and Engineering Faculties of the University of Florence, focuses on certain theoretical concepts and reference apparatus, bringing international literature to bear on the specific case of Italy. [italian version]